1964
DOI: 10.1073/pnas.51.6.1151
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Synthesis of Ribosomal Rna in Escherichia Coli by Levorphanol

Abstract: Note added in proof: Since this manuscript was submitted, Kallos and Rizok'2 have obtained direct chemical evidence indicating that the pipsyl as well as the tosyl group is covalently bonded to a serine residue of yCHT.We are indebted to Dr. Allen Gold for the gift of phenylmethanesulfonyl fluoride used to prepare PMS--yCHT in the early stages of this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1966
1966
1996
1996

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…BPI was isolated from rabbit PMN as previously described (1 (5, 6, unpublished observations) indicating that BPI-envelope interactions with all three strains are essentially the same. The bacteria were grown in a triethanolamine-buffered (pH 7.75-7.9) minimal salts medium (7). Stationary phase overnight cultures were transferred to fresh medium (diluted 1:10) and the subcultures were grown to midlogarithmic phase (3-4 h at 370C; 6-10 X 10' bacteria/ ml).…”
Section: Methodsmentioning
confidence: 99%
“…BPI was isolated from rabbit PMN as previously described (1 (5, 6, unpublished observations) indicating that BPI-envelope interactions with all three strains are essentially the same. The bacteria were grown in a triethanolamine-buffered (pH 7.75-7.9) minimal salts medium (7). Stationary phase overnight cultures were transferred to fresh medium (diluted 1:10) and the subcultures were grown to midlogarithmic phase (3-4 h at 370C; 6-10 X 10' bacteria/ ml).…”
Section: Methodsmentioning
confidence: 99%
“…Since the effect was more pronounced on ribosomes or rRNA formation than on sRNA, it is also possible that quinacrine produced a 'shift-down' effect. Other drugs, such as dinitrophenol (Simon, van Praag & Aronson, 1966), levorphanol (Simon & van Praag, 1964;Greene & Magasanik, 1967), and azide and cyanide (Nazar & Wong, r 969) have been observed to produce selective inhibition of RNA synthesis, particularly of rRNA, resembling the action of a more limited nutritive growth medium. Recently it was suggested that salicylate also exhibited such an action in B. cereus (Schwartz & Mandel, The normal messenger activity of RNA makes it doubtful that the quinacrine effect was specifically localized at the step of transcription to form mRNA.…”
Section: L Seligman a N D H G M A N D E Lmentioning
confidence: 99%
“…Escherichia coli J5, a rough UDP-galactose-4-epimerase negative mutant of the smooth strain 011 1-B4, and the smooth strains E. coli ML-35 (i-, y-, z+) (a generous gift of R. Lehrer, Department of Medicine, UCLA Center for the Health Sciences, Los Angeles, CA) and E. coli 09 were grown in triethanolamine buffered (pH 7.7-7.9) minimal salts medium (13). Other rough strains ofE.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%